A transducer based on amorphous alloy
By designing bridge wire, bridge film and bridge belt transducer elements using amorphous alloy materials, the problems of limited energy output and insufficient reliability of traditional pyrotechnic products are solved, and more efficient power conversion and safe and reliable pyrotechnic products are achieved.
Patent Information
- Application Number
- CN202310516775.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-09
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2043-05-09
AI Technical Summary
Due to material limitations, traditional pyrotechnic products have limited output energy, and are fast in action under electrical stimulation but lack of reliability, making it difficult to meet the needs of miniaturization and integration development.
Amorphous alloys are used as the transgenic element material, and the enthalpy change reaction energy is released through electrothermal effect and crystallization reaction, and the transgenic element of bridge wire, bridge film and bridge belt type is designed.
It improves the safety and reliability of pyrotechnic products, achieves more efficient power conversion and delayed discharge, and meets the performance requirements of different types of pyrotechnic products.
Smart Images

Figure CN116497258B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of pyrotechnics, and in particular relates to an energy conversion element based on an amorphous alloy. Background Art
[0002] The transducer is the core component of pyrotechnics to achieve energy initiation and energy conversion, and is also the key to achieving low-energy ignition and high energy conversion efficiency of pyrotechnic transducer devices. With the development trend of miniaturization and integration of pyrotechnics, traditional pyrotechnics have limited output energy due to limitations in materials and other aspects. In addition, under electrical stimulation, the transducer acts quickly, and the reliability of pyrotechnics is problematic. Therefore, exploring new materials and processes to develop new pyrotechnics to improve the safety and reliability of pyrotechnics is one of the important directions for the current development of pyrotechnics.
[0003] At present, energy conversion elements often use nickel-chromium alloy, pure metal film, polysilicon semiconductor and other materials to achieve the electrothermal energy conversion of pyrotechnics. Bridge wire, bridge film and bridge belt are the three most commonly used energy conversion device forms of pyrotechnics energy conversion elements. Nickel-chromium alloy is the most commonly used energy conversion element material. Its principle is to stimulate energetic materials by generating electrothermal effect through external electric energy. Zhou Qing, Jiao Qingjie. Ignition law of Ni-Cr bridge wire type pyrotechnics [J]. Journal of Sichuan Ordnance, 2015, 36(4): 144-147 discloses the ignition performance of Ni-Cr bridge wire type energy conversion element, and studies and analyzes the influence of base material and bridge wire diameter. Wang Kewei, Yang Zhengcai, Liu Haixu, et al. Preparation and performance of insensitive Ni-Cr metal bridge film transducer [J]. Energetic Materials, 2014 (6): 819-823. A Ni-Cr thin film bridge transducer prepared by magnetron sputtering technology is disclosed. The size is 400μm×380μm×2.8μm and the resistance is 1Ω. A new type of bridge film transducer suitable for insensitive pyrotechnics is obtained. Xu Chao, Li Zhaoze, Wan Hong, et al. Research on Cr thin film ignition resistor in MEMS solid micro-thruster [J]. Journal of Sensor Technology, 2006, 19 (5): 1411-1414, 1418. A Cr thin film ignition resistor is prepared by magnetron sputtering coating, photolithography and wet etching of Cr using metal Cr as the ignition resistor material, and the ignition of RDX at a low voltage of 20V is realized. Polysilicon is another energy conversion material commonly used in semiconductor bridge pyrotechnics. Polysilicon is often heavily doped with P or B elements to give the material excellent semiconductor conductivity. Currently, there are many types of conventional polysilicon semiconductor bridges, single-layer / multi-layer metal composite semiconductor bridges, and energetic semiconductor bridges. Shen Ruiqi's team at Nanjing University of Science and Technology has studied the application of energetic films in semiconductor bridge pyrotechnics such as Al / Ni, B / Ti, Al / CuO, Zr / CuO, and Mg / CuO, and proved that the Al / CuO energetic composite film can undergo an electric explosion reaction under electrical excitation conditions, generating redox chemical reaction heat between the Al film and the CuO film in addition to Joule heat, so that the product of the electric explosion reaction forms a high-temperature plasma, achieving output energy doubling.
[0004] In recent years, researchers have also explored some new energy conversion element materials, including carbon film energy conversion elements, tantalum nitride energy conversion elements and energetic MOFs. Zhu Shunguan's team at Nanjing University of Science and Technology adopted the overall design concept of energy conversion structure based on carbon materials, and designed and prepared carbon film energy conversion elements through processes such as high-temperature pyrolysis, spraying and chemical vapor deposition. The study found that the carbon film bridge has higher energy utilization and stronger ignition ability than semiconductor bridges and bridge wire pyrotechnics; the ignition range is narrow, with good anti-static ability, which improves the safety and reliability of pyrotechnics. Ren Xiaoming, Liu Lan, Yu Kexin, et al. Research on low energy conversion of tantalum nitride thin film energy conversion elements [J]. Pyrotechnics, 2021 (1): 5-8. A design and preparation method of tantalum nitride thin film energy conversion element is disclosed. Different factors such as bridge film thickness, bridge area size, and bridge area shape affect the ignition of the energy conversion element. By optimizing the bridge area size and shape, the minimum average ignition voltage of the tantalum nitride thin film energy conversion element obtained is less than 5V. Zhang Wenchao et al. disclosed an energetic MOFs thin film semiconductor bridge and its preparation method in patent CN 107631664 A. The MOFs in thin film form are assembled onto the surface of the semiconductor bridge chip by a nano-spraying method. The energetic MOFs generate a composite flame of high-temperature plasma and high-temperature splashes during the ignition of pyrotechnics, thereby increasing the output energy and the ignition capability of lead styphnate and lead azide.
[0005] Amorphous alloys are a new type of metal material that uses metallurgical rapid solidification technology and entropy control concepts to suppress the crystallization of alloy melt atoms and maintain and control the disordered structural characteristics of the melt. The main characteristics of amorphous alloys are disordered composition and long-range disordered atomic structure, and the absence of defects such as grain boundaries and stacking faults. There are currently no reports on the use of amorphous alloys as pyrotechnic energy conversion materials. Summary of the invention
[0006] The object of the present invention is to provide an energy conversion element based on an amorphous alloy.
[0007] The technical solution to achieve the purpose of the present invention is: an energy conversion element based on an amorphous alloy, wherein the energy conversion element is a bridge wire type, a bridge membrane type or a bridge belt type;
[0008] The bridge wire, bridge membrane and bridge belt are all made of amorphous alloy;
[0009] Amorphous alloys include the following elements: Ni, Fe, B, Mo, V, Co, P, Cu, Ti, Zr, Si.
[0010] Furthermore, the general formula of amorphous alloy is: Fe a Ni b B c Mo d V e Co f P g Cuh Ti i Zr j Si k , where a, b, c, d, e, f, g, h, i, j, and k are atomic percentages, and their value ranges are: 10<a<50, 0≤b<70, 0≤c<30, 0≤d≤5, 0≤e≤5, 0≤f<70, 0≤g≤5, 0≤h<30, 0≤i<40, 0≤j<40, 0≤k≤10.
[0011] Furthermore, the energy conversion element is of bridge wire type, the amorphous alloy bridge wire is cylindrical, the resistance value ranges from 1Ω to 7Ω, the diameter is between 9μm and 30μm, and the length is 2±0.2mm.
[0012] Furthermore, the amorphous alloy bridge wire is welded to the electrode plug pad or foot wire of the energy conversion element by soldering.
[0013] Furthermore, the energy conversion element is of a bridge film type, and the energy conversion element includes an amorphous alloy film bridge area, a substrate and a conductive pad;
[0014] The size of the amorphous alloy thin film bridge area is: length×width×thickness=(100 μm-300 μm)×(100 μm-300 μm)×(1 μm-2 μm), and the resistance is 1Ω±0.1Ω.
[0015] Furthermore, the amorphous alloy thin film bridge region is in the shape of an “I”, a quadrilateral, a double “V”, a double arc, or a sawtooth;
[0016] The substrate is ceramic, alumina, doped alumina, phenolic resin or sapphire.
[0017] Furthermore, the amorphous alloy film is first formed by magnetron sputtering, and then a film bridge region of a desired shape is obtained by femtosecond or picosecond laser processing.
[0018] Furthermore, the energy conversion element is of bridge-belt type, and the energy conversion element includes large-area heat dissipation areas in the form of sheets at both ends and a thin waist-shaped heat collection area in the middle;
[0019] The heat collection area is made of amorphous alloy, namely, an amorphous alloy bridge strip, the thickness of the amorphous alloy bridge strip is 15 μm to 30 μm, and the resistance is 1Ω±0.1Ω.
[0020] Furthermore, the narrow waist and narrow gap of the amorphous alloy heat collection area is 0.15mm to 0.30mm.
[0021] Furthermore, the amorphous alloy bridge strip is prepared by wire cutting.
[0022] Compared with the prior art, the present invention has the following significant advantages:
[0023] (1) The process is mature and simple, and can be prepared and used in large quantities. The amorphous alloy transducer only uses amorphous alloy materials to replace existing materials, and the manufacturing processes of the three transducers, namely bridge wire, bridge membrane and bridge belt, can achieve seamless connection;
[0024] (2) Under electrical excitation, the amorphous alloy transducer can produce both electrothermal effect and crystallization reaction to release enthalpy change reaction energy, eliminating the use of highly sensitive detonators and improving the safety and reliability of the transducer;
[0025] (3) Amorphous alloys have high resistance in the amorphous state, which is conducive to the electrothermal effect. g Point (glass transition point), after the amorphous material changes into the crystalline material, the resistance will decrease, that is, the negative temperature effect of the resistance will be generated, which will delay the discharge and improve the conversion efficiency of electric energy;
[0026] (4) The material has strong selectivity and plasticity. Different amorphous components can be selected and prepared into various forms of energy conversion elements to meet the performance requirements of different types of pyrotechnics. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is a schematic diagram of the amorphous alloy bridgewire type energy conversion element of the present invention.
[0028] Figure 2 It is a schematic diagram of the amorphous alloy bridge film type energy conversion element of the present invention.
[0029] Figure 3 It is a schematic diagram of the amorphous alloy bridge-belt type energy conversion element of the present invention. DETAILED DESCRIPTION
[0030] The present invention is further described in detail below in conjunction with the accompanying drawings.
[0031] The present invention provides an initiator energy conversion element based on an amorphous alloy, including three forms: a bridge wire, a bridge film and a bridge belt. The composition of the amorphous alloy can be adjusted by combining different component elements.
[0032] When working, the power supply is connected to the two ends of the foot wire or the pad, and a constant current or constant voltage capacitor discharge is passed between the two electrodes. The electrothermal effect and crystallization conversion energy of the amorphous alloy are used to make the amorphous alloy wire / film / ribbon quickly heat up, and even generate plasma, thereby playing the role of ignition or explosion. By selecting different amorphous components and preparing different forms of energy conversion elements, the use requirements of different types of pyrotechnics can be met.
[0033] The energy conversion element of the pyrotechnic device based on amorphous alloy includes three forms: bridge wire, bridge film and bridge belt. The amorphous alloy contains the following elements: Ni, Fe, B, Mo, V, Co, P, Cu, Ti, Zr, Si. It can be expressed by the general formula: Fe a Nib B c Mo d V e Co f P g Cu h Ti i Zr j Si k Wherein, a, b, c, d, e, f, g, h, i, j, k are atomic percentages, and their variation range is 10<a<50, 0≤b<70, 0≤c<30, 0≤d≤5, 0≤e≤5, 0≤f<70, 0≤g≤5, 0≤h<30, 0≤i<40, 0≤j<40, 0≤k≤10.
[0034] The preparation steps of the amorphous alloy of the bridgewire type amorphous alloy energy conversion element are as follows:
[0035] (1) The alloy ingredients are weighed according to the atomic percentage and placed in a vacuum-sealed copper crucible.
[0036] (2) The mixed material in step (1) is subjected to multiple arc melting or induction melting in a high-purity argon atmosphere, assisted by turning and electromagnetic stirring to mix the components uniformly, and then cooled to obtain a master alloy ingot.
[0037] (3) The master alloy ingot in step (2) is crushed and placed in a quartz tube for remelting. The master alloy is melted by induction by electricity. The melt is ejected and contacts a high-speed rotating copper wheel, and is rapidly cooled to obtain an amorphous alloy.
[0038] (4) The amorphous alloy obtained in step (3) is welded to the two ends of the foot wire on the electrode plug by welding technology, so that the amorphous wire and the foot wire are connected together.
[0039] The rapid cooling of the amorphous alloy is carried out in a high vacuum argon atmosphere; the high temperature heating temperature is 1000 to 2000 degrees Celsius.
[0040] The amorphous alloy bridge wire type transducer bridge wire is soldered to the electrode plug pad or foot wire, and the resistance value is adjusted by the alloy composition and bridge wire diameter. The amorphous alloy is cylindrical wire with a resistance range of 1Ω to 7Ω, a diameter of 9μm to 30μm, and a length of about 2mm.
[0041] The amorphous alloy in the amorphous alloy bridge film transducer is in the form of a thin film, and the transducer consists of three parts: an amorphous alloy thin film bridge area, a substrate, and a conductive pad. The size of the thin film bridge area is: length × width × thickness = (100μm ~ 300μm) × (100μm ~ 300μm) × (1μm ~ 2μm), and the resistance is 1Ω ± 0.1Ω. The shape can be "I" shape, quadrilateral, double "V" shape, double arc shape, and sawtooth shape. The amorphous alloy film is formed by magnetron sputtering technology, and the thin film bridge area is obtained by femtosecond or picosecond laser processing. The substrate materials are ceramics, alumina, doped alumina, phenolic resin, and sapphire.
[0042] The structure of the amorphous alloy bridge-belt type energy conversion element includes large-area sheet-shaped heat dissipation areas at both ends and a thin waist-shaped heat collection area in the middle, with a thickness of 15μm to 30μm and a narrow slit width of 0.15mm to 0.30mm. The bridge belt is made by wire cutting technology and has a resistance of 1Ω±0.1Ω.
[0043] Example 1: Figure 1 As shown, the amorphous alloy energy conversion element is a bridge wire type, and its composition is Fe 15 Ni 65 B 20 , initial resistance 1.5Ω, diameter 25μm, length 2mm. The amorphous alloy bridge wire was dipped in lead styphnate for ignition experiment, the minimum current for 100% ignition was 2.7A, and the maximum current for 100% non-ignition was 1.9A.
[0044] Example 2: Figure 2 As shown, the amorphous alloy energy conversion element is a bridge film type, and its composition is Fe 20 Ni 57.5 Mo 2.5 B 20 The bridge area is double "V" shaped, with a horizontal length of 240μm, a width of 286μm, and a "V" angle of 120°. Under the discharge condition of a 47μF tantalum capacitor, the minimum voltage for 100% ignition is 21.3V, and the maximum voltage for 100% non-ignition is 12.5V.
[0045] Embodiment 3: Figure 3 As shown, the amorphous alloy energy conversion element is a bridge-band type, and its composition is Fe 59.8 Ni 20 V 0.2 B 20 The width of the heat collection area is 0.2mm, the length is 2.4mm, and the heat dissipation area is 0.83mm 2 The ignition charge is Zr / KClO4, the minimum current for 100% ignition is 4.65A, and the maximum current for 100% non-ignition is 3.79A.
Claims
1. A transducer based on an amorphous alloy, characterized in that: The energy conversion element is of bridge wire type, bridge membrane type or bridge belt type; The bridge wire, bridge membrane and bridge belt are all made of amorphous alloy; The general formula of amorphous alloy is: Fe a Ni b B c Mo d V e Co f P g Cu h Ti i Zr j Si k , where a, b, c, d, e, f, g, h, i, j, and k are atomic percentages, and their value ranges are: 10<a<50, 0≤b<70, 0≤c<30, 0≤d≤5, 0≤e≤5, 0≤f<70, 0≤g≤5, 0≤h<30, 0≤i<40, 0≤j<40, 0≤k≤10.
2. The energy conversion element according to claim 1, characterized in that: The energy conversion element is of bridge wire type, the amorphous alloy bridge wire is cylindrical wire-shaped, the resistance value ranges from 1Ω to 7Ω, the diameter is between 9μm and 30μm, and the length is 2±0.2mm.
3. The energy conversion element according to claim 2, characterized in that: The amorphous alloy bridge wire is welded to the electrode plug pad or foot wire of the energy conversion element by soldering.
4. The energy conversion element according to claim 1, characterized in that: The energy conversion element is of bridge film type, and the energy conversion element comprises an amorphous alloy thin film bridge area, a substrate and a conductive pad; The size of the amorphous alloy thin film bridge area is: length×width×thickness=(100μm~300μm)×(100μm~300μm)×(1μm~2μm), and the resistance is 1Ω±0.1Ω.
5. The energy conversion element according to claim 4, characterized in that: The amorphous alloy film bridge area is in the shape of an "I" character, a quadrilateral, a double "V" character, a double arc, or a sawtooth shape; The substrate is ceramic, phenolic resin or sapphire.
6. The energy conversion element according to claim 5, characterized in that: The amorphous alloy film is first formed by magnetron sputtering and then processed by femtosecond or picosecond laser to obtain the film bridge region of the desired shape.
7. The energy conversion element according to claim 1, characterized in that: The energy conversion element is of bridge-belt type, and includes large-area heat dissipation areas in the form of sheets at both ends and a thin waist-shaped heat collection area in the middle; The heat collection area is made of amorphous alloy, namely, an amorphous alloy bridge strip, the thickness of the amorphous alloy bridge strip is 15 μm to 30 μm, and the resistance is 1Ω±0.1Ω.
8. The energy conversion element according to claim 7, characterized in that: The narrow waist and narrow gap of the amorphous alloy collector area are 0.15mm~0.30mm.
9. The energy conversion element according to claim 8, characterized in that: The amorphous alloy bridge strips were prepared by wire cutting.
Citation Information
Patent Citations
Energetic MOFs thin-film semiconductor bridge and preparation method thereof
CN107631664A
Iron-based amorphous alloy powder, iron-based amorphous alloy coating and preparation method thereof
CN102534435A
Iron-based block amorphous alloy with invar effect and preparation method thereof
CN102758151A